Flexibility in natural gas : supply and demand - Cornot-Gandolphe, Sylvie; Dickel, Ralf; Organisation for Economic Co-operation and Development; International Energy Agency (Paris : OECD/IEA, 2002)
'In most IEA Member countries, natural gas demand varies strongly during the year, according to temperature. Flexibility is needed to cover seasonal swings and variations in gas demand, especially for household customers. It is also needed to maintain short-term supply security in the case of a disruption of a supply source. Over the years, gas companies have devised a variety of flexibility tools, such as supply swing, storage and interruptible contracts. This enabled them to balance supply and demand by modifying volumes. Today, market liberalisation encourages the development of hubs and spot markets, where supply and demand can be balanced by the pricing mechanism. As a result, flexibility services are now offered and priced independently from the gas itself. Opportunities for arbitrage between gas and electricity have also emerged in countries where both sectors have been liberalised'-P. [4] of cover.
'The main author of this book is Sylvie Cornot-Gandolphe. Ralph Dickel, Head of the Energy Diversification Division, directed the project and provided valuable input and advice'--P. 5.
References : p. 269-273
Keywords: Natural gas -- Europe; Gas industry -- Europe; Supply and demand